The microbiome: a link between obesity and breast cancer risk - Gaber, Mohamed; Arnone, Alana A.; Vidi, Pierre-Alexandre; Cook, Katherine L. (Frontiers in Microbiomes, 2024)
Globally, breast cancer is the leading cause of cancer incidence and mortality among all female cancers. Hereditary factors only account for 5-10% of breast cancers, highlighting the importance of non-hereditary factors, such as obesity. The increasing prevalence of obesity underscores the need to understand its contribution to breast cancer risk. Multiple mechanisms may mediate pro-carcinogenic effects of obesity, including altered adipokine levels, local and systemic inflammation, disruption of insulin and insulin-like growth factor signaling, increased estrogen levels, and alterations of the microbiome. In this review, we focus on the link between gut microbiome alterations and breast cancer risk in the context of obesity. First, we discuss how obesity influences the gut microbiome. Next, we describe the effect of such microbiome alterations on breast carcinogenesis, highlighting underlying molecular mechanisms. Finally, we review preclinical data on the interactions between host and bacteria, current challenges to study the obesity-microbiome connection, and future perspectives in this field.